2007 IEEE International Parallel and Distributed Processing Symposium 2007
DOI: 10.1109/ipdps.2007.370408
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating Data Parallel SAC Programs with S-Net

Abstract: We propose a two-layered approach for exploiting different forms of concurrency in complex systems: We specify computational components in our functional array language SaC, which exploits data parallel properties of array processing code. The declarative stream processing language S-Net is used to orchestrate the collaborative behaviour of these components in a streaming network. We illustrate our approach by a hybrid implementation of a sudoku puzzle solver as a representative for more complex search problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
2
2
2

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…A smaller scale case study on the interplay between S-Net and the functional array language SaC [26] as component implementation language can be found in Ref. [17]. The theme here is the concurrent solving of Sudoku puzzles, which we deem representative for a relevant class of search problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A smaller scale case study on the interplay between S-Net and the functional array language SaC [26] as component implementation language can be found in Ref. [17]. The theme here is the concurrent solving of Sudoku puzzles, which we deem representative for a relevant class of search problems.…”
Section: Discussionmentioning
confidence: 99%
“…We refer the reader interested into the interplay between box language and S-Net to Ref. [17] for a more elaborate case study.…”
Section: Example: Stream Of Factorial Numbersmentioning
confidence: 99%
“…User applications simply perceive the computing element as an intelligent memory that can perform operations on its data. The interface memories also isolate the internal architecture of the element from the comunication network; the computing elements can be connected either directly to a processor bus as shown in Figure 3 (this case will be discussed in the following text), or they can be connected in a specialized network topology constructed with respect to the flow of data in the application, as offered by the recently researched component approaches [13], [14].…”
Section: User-level Interface and System Integrationmentioning
confidence: 99%
“…The first comprehensive solution for S-Net was by Grelck and Shafarenko (see [20], where the language definition and some relevant algorithms are presented). Further development of the type system was done by Cai et al [21] and some recent examples of the use of S-Net in applications are found in [18].…”
Section: Related Workmentioning
confidence: 99%
“…To support the parallel component technology being discussed, a coordination language has been designed and implemented [20,18]. The language is called S-Net, which stands for Streaming Networks.…”
Section: Languagementioning
confidence: 99%